Germany: Policies for Internationalization - Pekşen, Sude; Leišytė, Liudvika (International Higher Education, 2021)
Germany has become a top destination for study abroad, owing to its longstanding and specific type of internationalization through nonprofit orientation and cooperation—a typical soft-power approach. The role of intermediary actors, especially the DAAD, has been crucial in this respect. Supportive measures are promoting internationalization at the federal and state levels. Meanwhile, the recent introduction of tuition fees in the southern states points to a slight distancing from Germany's traditional nonprofit orientation.